(untitled) (International Journal of Environmental Sciences, 2025)
Jurists have mentioned that bribery is what is given to invalidate a right or justify falsehood, and it is considered one of the major sins. Exceptions are made for those who bought off with his money in cases of necessity, and the sin then falls on the receiver unjustly, not on the compelled giver. They exemplified buy-off by lifting the aggression of an oppressor, a highwayman, or someone threatened with murder, and contemporaries have likened it to the arbitrariness of customs officials, and the like in buy-off applications. This research highlights this term while monitoring the most important jurisprudential rulings related to it. The Kingdom of Saudi Arabia has made significant progress in eradicating corruption in all its forms, including financial corruption, and is striving towards a clean, clear, and transparent financial economy. Every financial buy-off that breaches the regulations of Sharia and civil laws is subject to monitoring by the competent authorities.